Reducing capital cost in Southern Africa (Development Centre studies., 2005)
The private sector and public authorities both need access to capital for investment, job creation and growth. For a number of reasons, explained in this book, Southern Africa suffers from disproportionately expensive capital and this is denying the region its full growth potential. This is a serious situation within the region, where public expectations of economic growth are being frustrated in South Africa, and in sub-Saharan Africa generally which relies on Southern Africa as both a source and a destination for investment. This book reflects the ideas and proposals of a group of experts and practitioners from the state and business environments, brought together by the Development Centre with public and private sector partners on reducing the cost of capital in the region. It provides insight into the nature of the problem of the cost of capital in Southern Africa and the effects it has on business activity and infrastructure development. In addition, the authors set out to define strategies for reducing capital cost, outlining measures suitable for government and private actors.--Publisher summary.